Technology-Based Physical Health Interventions for Adults with Intellectual Disability: A Scoping Review - Savage, Melissa N.; Clark, Tina A.; Baffoe, Edward; Candelaria, Alexandra E.; Aneke, Lola; Gonzalez, Renee; Al Enizi, Ali; Anguita-Otero, Marisol; Edwards-Adams, Keita; Grandberry, Lilliesha; Reed, Stella (Journal of developmental and physical disabilities, 2024)
Physical health habits including physical activity and nutrition are essential for numerous health benefits. However, beginning in childhood, individuals with intellectual disability engage in lower levels of physical activity and healthy nutrition habits compared to individuals without intellectual disability, a trend that carries on into adulthood. Researchers continue to examine the effectiveness of interventions to increase engagement in physical health habits and improve health outcomes for individuals with intellectual disability, with an increased focus on technology-based interventions. This scoping review aimed to describe how technology was being utilized within interventions to improve health-related outcomes for adults with intellectual disability. We described the technology being used, who used the technology, and the feasibility of the interventions. Forty-one studies met criteria, with a total of 698 adult participants with an intellectual disability. While no studies on nutrition were located, technology was used in various physical activity interventions, with the most common being preferred stimulus access, exergaming, and video-based instruction. Most studies took place at day or rehabilitation centers, were implemented by research teams, and either did not discuss cost or were vague in their description related to cost. Implications, limitations, and future research directions are discussed.